Factors Affecting the Satisfaction Level of Gastronomy Tourist Among Inbound ASEAN: Post Covid-19 Analysis - Kugeneswary Thanasegaran,; R. Chandrashekar, (Research in Management of Technology and Business, 2023)
Gastronomy tourism experiences are growing in the tourism industry and there has been an increase in the number of tourists that travel primarily to experience food and related culture. Gastronomy tourists mostly focuses on their satisfaction level as their expectations will lead them to travel for the food. However, there are limited amount of information available about what is affecting the fast-growing Malaysian gastronomical tourism, especially in the post covid-19 recovery environment. Therefore, this study will be conducted as a reference to know more details about factors related to the growth of inbound ASEAN tourists in Malaysia. The objective of conducting this study is to identify the factors affecting the satisfaction level of gastronomy tourist and to identify the satisfaction level of gastronomy tourist. This study also aims to identify the relationship between the factors and satisfaction level of gastronomy tourist. Researcher has decided to conduct the survey at Kuala Lumpur. The target population of respondent for this study is inbound ASEAN tourist. The study employed quantitative research approach to conduct the survey. A questionnaire was established and distributed to targeted tourist. There were five factors been analysed in this research and the result indicates that all factors in this research is significant and have a relationship with tourist satisfaction except for food-related personality traits which is significant but have none relationship with tourist satisfaction. Based on the result, the major factor that affects the satisfaction level of gastronomy tourist is the motivational factor.